Legality closure of the Strait of Hormuz in perspective of the 1982 United Nations Convention on the Law of the Sea - Muhammad Bagas Amart Syahputra; Muhammad Rahmadhan; Muhammad Farhan Harry Perdana; Ema Septaria (Privietlab, 2026)
The Strait of Hormuz is one of the world's most strategically important international straits, serving as a critical route for global energy transportation and international maritime navigation. Renewed geopolitical tensions have revived debates over the legality of its potential closure, particularly by Iran, on national security grounds. Despite extensive discussions on the geopolitical significance of the Strait, limited legal scholarship has specifically examined the extent of coastal State authority to restrict transit passage under the 1982 United Nations Convention on the Law of the Sea (UNCLOS). This study analyzes the legality of closing the Strait of Hormuz using a normative legal approach that employs statutory, conceptual, and comparative analyses of relevant international legal practices. The findings demonstrate that the Strait of Hormuz constitutes a strait used for international navigation and is therefore governed by the transit passage regime under the UNCLOS, particularly Articles 37, 38, 39, 42, and 44. Under this regime, Coastal States may adopt limited regulatory measures consistent with Article 42, provided that such measures do not deny, hamper, or impair transit passage. They may not suspend transit passage under Article 44. Accordingly, the study concludes that the unilateral closure of the Strait of Hormuz would be incompatible with the legal framework established by the UNCLOS and would undermine legal certainty, freedom of navigation, and stability of the international maritime order.